Reducing the “ouch” after phototherapy in neonates!! – A prospective observational study to prove the correlation of transcutaneous and serum bilirubin after cessation of phototherapy - Varughese, Pearl Mary (Indian Journal of Child Health, 2019)
Background: Neonates receiving phototherapy (PT) for neonatal hyperbilirubinemia are often discharged late and multiple blood samples are taken during and after discontinuation of PT. Clinicians often have reservations in replacing total serum bilirubin (TSB) with transcutaneous bilirubinometer (TcB). Objective: The objective of the study was to study the correlation between TcB values with TSB in infants before PT and during rebound bilirubin assessment in term and late preterm babies. Materials and Methods: The study was conducted in a tertiary newborn center from November 2014 to June 2016. The babies above 34 weeks gestation period significant hyperbilirubinemia were included in the study and exclusion criteria included babies with established direct hyperbilirubinemia, neonatal septicemia, major congenital/gastrointestinal malformations, and those on PT. TSB and TcB were taken at 24 h of age in all babies and rebound values, both TSB and TcB, in 54 babies who required PT. Statistical analysis was done using Spearman’s correlation and Bland Altman plots. Results: TcB and TSB showed good correlation (Spearman R=0.917) at 24 h of age before initiation of PT but with poor agreement (mean difference overestimating by 1.5 mg/dl). The correlation of TcB and TSB at the time of rebound estimation was 0.994 with good agreement (mean difference overestimating by 0.6 mg/dl). Conclusion: Pediatricians should take steps in reducing “ouch” for rebound bilirubin.